Alternatives to antibiotics in a One Health context and the role genomics can play in reducing antimicrobial use. (December 2020) - Pollock, J.; Low, A.S.; McHugh, R.E.; Muwonge, A.; Stevens, M.P.; Corbishley, A.; Gally, D.L.
Abstract: Background: This review follows on from the International Conference on One Health Antimicrobial Resistance (ICOHAR 2019), where strategies to improve the fundamental understanding and management of antimicrobial resistance at the interface between humans, animals and the environment were discussed. Objective: This review identifies alternatives to antimicrobials in a One Health context, noting how advances in genomic technologies are assisting their development and enabling more targeted use of antimicrobials. Sources: Key articles on the use of microbiota modulation, livestock breeding and gene editing, vaccination, antivirulence strategies and bacteriophage therapy are discussed. Content: Antimicrobials are central for disease control, but reducing their use is paramount as a result of the rise of transmissible antimicrobial resistance. This review discusses antimicrobial alternatives in the context of improved understanding of fundamental host–pathogen and microbiota interactions using genomic tools. Implications: Host and microbial genomics and other novel technologies play an important role in devising disease control strategies for healthier animals and humans that in turn reduce our reliance on antimicrobials. Graphical abstract: Summary of alternatives to antibiotics in One Health context. Image 1